Simulation, optimization and parametric studies of a solid catalyzed gas phase ethylene polymerization fluidized bed reactor - Ghasem, N.M.; Sulaiman, M.Z.; Hussain, Mohd Azlan (Society of Chemical Engineers, Japan, 2005)
A steady-state model incorporating interactions between separate bubbles and emulsion phases in a fluidized-bed polyethylene reactor is employed to study the effect of operating conditions on the stability of gas-phase polyethylene reactors. A simple optimization program is developed to find the optimum combination of operating parameters at which the maximum polyethylene production rate is achieved with the constraints only on the reactor temperature, which should not exceed the melting point of polymer. Using the optimum values found, the parametric investigation for the effect of the catalyst deactivation rate constant and process operating parameters, such as the catalyst feed rate and the gas superficial to minimum fluidization velocity on system behavior are investigated. The investigations reveal that, the fluidized bed polyethylene reactor is prone to show unstable behavior and temperature oscillations, and the optimum polyethylene production rate could be achieved when it operates close to its melting point under a suitable controller to avoid polymer melting. Copyright Â© 20